2023
DOI: 10.3390/ma16031073
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Chirality in Atomically Thin ZnSe and CdSe Nanoplatelets: Strengthening of Circular Dichroism via Different Coordination of Cysteine-Based Ligands on an Ultimate Thin Semiconductor Core

Abstract: Chiral nanostructures exhibiting different absorption of right- and left-handed circularly polarized light are of rapidly growing interest due to their potential applications in various fields. Here, we have studied the induction of chirality in atomically thin (0.6–1.2 nm thick) ZnSe and CdSe nanoplatelets grown by a colloidal method and coated with L-cysteine and N-acetyl-L-cysteine ligands. We conducted an analysis of the optical and chiroptical properties of atomically thin ZnSe and CdSe nanoplatelets, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Chiral ligands on the surface of the NPL are able to transfer their mirror asymmetry to the excitations in the semiconductor core NPL, thus inducing the chirality of the entire system. This phenomenon has been called chirality transfer and has been actively discussed recently [ 2 , 3 , 26 , 32 ]. The chiroptical properties of NPLs acquired in this way and the efficiency of chirality transfer in the case of chiral amino acid ligands were investigated using CD spectroscopy and demonstrated in Figure 6 c,d.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chiral ligands on the surface of the NPL are able to transfer their mirror asymmetry to the excitations in the semiconductor core NPL, thus inducing the chirality of the entire system. This phenomenon has been called chirality transfer and has been actively discussed recently [ 2 , 3 , 26 , 32 ]. The chiroptical properties of NPLs acquired in this way and the efficiency of chirality transfer in the case of chiral amino acid ligands were investigated using CD spectroscopy and demonstrated in Figure 6 c,d.…”
Section: Resultsmentioning
confidence: 99%
“…The position of the maxima corresponds with the transition bands in the absorption spectra and indicates the excitonic nature of CD transitions. Unlike the sulfur-containing ligands described earlier [26,32], CD bands corresponding to heavy and light holes (around 390 and 370 nm correspondingly) have the same sign, which is similar to the case described for zinc blende with L-cysteine ligand on the surface [24,25]. However, a CD band corresponding to a spin-orbit hole with a positive sign at around 350 nm is visible only for the CdSe394Ala sample, possibly due to better passivation for the L-alanine ligand.…”
Section: Analysis Of Optical and Chiroptical Propertiesmentioning
confidence: 96%
See 2 more Smart Citations
“…[26]. It was shown that L/D cysteine and N-acetylcysteine ligands induce different signs of circular dichroism at the same absolute configuration for both 0D CdSe quantum dots and 2D CdSe nanoplatelets [27,28]. The change in the sign of the CD is due to a change in ligand coordination when replacing cysteine with acetylcysteine, leading to a change in the orientation of the molecular dipole and the exciton dipole in the core.…”
Section: Introductionmentioning
confidence: 99%